Plant disease epidemiology: A quantitative approach on phytopathology = Epidemiología agrícola: Un enfoque cuantitativo de la fitopatología - Pedroza Sandoval, Aurelio (International Center for Tropical Agriculture, 1995)
A new technological approach in crop production is required in order to increase a sustainable food production, it keeping the agroecosystem balance. A new approach to do agriculture needs taking advantage of the inter and multidisciplinary participation of different specialities in emergent areas, such as, System Theory, Biotechnology, Environment Impact, Geographical Information Systems, Sustainable Agriculture, Expert Systems, and Plant Disease Epidemiology. Epidemic triangle host-pathogen-environment has been recognized as an integrated factor in plant disease epidemiology, which, currently is a useful phytopathological tool to quantify the diseases prevent the damage caused by plant pathogens. Important surveys about Comparative Epidemiology were conducted as a result of development in plant disease epidemiology in order to achieve better strategies in plant disease management.